Continuities in Highland Maya Social Organization : Ethnohistory in Sacapulas, Guatemala - Hill II, Robert M.; Monaghan, John (Ethnohistory series (Philadelphia, Pa.), 1987)
Continuities in Highland Maya Social Organization innovatively combines ethnohistoric, ethnographic, and archaeological research to present the first study of the Maya community from preconquest to modern times.